THE USE OF MUSICAL GAMES IN MUSIC LESSONS AND EXTRACURRICULAR ACTIVITIES AND THEIR SIGNIFICANCE - S. M. Asqarova (Galaxy International Interdisciplinary Research Journal, 2023)
This article discusses the use of musical games in music lessons and extracurricular activities, emphasizing their importance and types. Examples of games suitable for both lessons and extracurricular time are provided.